A parametric study of a hybrid battery thermal management system that couples PCM with wavy microchannel cold plate. (25th January 2023) - Wang, Yonghao; Gao, Tieyu; Zhou, Liang; Gong, Jianying; Li, Jun
Highlights: A hybrid cold plate for cylindrical lithium-ion cells is designed. Increasing d and h1 / h2 can increase the heat storage capacity. Cross flow significantly improves the utilization of PCM. The mass flow rate needs to match the phase transition temperature. Abstract: In the actual use of electric vehicles, the battery will face complex and changeable working conditions, and the battery thermal management system (BTMS) is of vital important. In this paper, an innovative system using PCM and wavy microchannel cold plate (WMCP) called hybrid wavy microchannel cold plate (HWMCP) is designed and its parameters are analyzed and optimized. The results indicate that the heat storage capacity of HWMCP increases with the increase of PCM thickness and height ratio h1/h2. The cooling capacity of HWMCP is slightly improved when the liquid microchannels grow in number. Compared with unidirectional flow, cross flow significantly reduces the maximum temperature of the battery and improves the utilization rate of PCM. For HWMCP, the mass flow rate should be matched with the phase transition temperature to avoid premature complete melting of the PCM. Besides, lower phase transition temperature could play the role of absorbing heat earlier, and the temperature of the battery pack also decreases more obviously. After parameter optimization, the maximum temperature of HWMCP is 2.3 k lower than that of WMCP at 400 s under pulsed heat load and the temperature difference is reduced by 0.5 K. Moreover, in cold weather, the HWMCP extends the time required for the battery pack to drop to the lowest appropriate operating temperature. The results of this study provide a reference for the design of HWMCP.